MANAGEMENT OF PEANUT BUD NECROSIS DISEASE IN GROUNDNUT THROUGH TOLERANT VARIETIES - GOPAL, K.; MUNIYAPPA, V.; JAGADESWAR, R.; VEMANA, K. (Annals of Agricultural Research, 2014)
Five groundnut varieties with different levels of resistance to PBND were experimented for three rainy and two post rainy seasons to analyse their effect on management of PBND. The results revealed that final PBND incidence, apparent infection rate. Area under disease progress curves (AUDPC) value were consistent with the respective variety. Further, 'TG-26' out yielded other varieties in terms of pod yield (1,112, 1,943 kg/ha in rainy and post rainy season respectively) with less apparent infection rate (0.003494) low PBND % (17.76) low AUDPC value (741) indicating its tolerance and better performance.